KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI SELF EFFICACY DALAM MATERI GEOMETRI KELAS XI SMK - Noviza, Trivanila; Hartoyo, Agung; Yani T, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research is a qualitative descriptive research that discusses mathematical problems solving that have high, medium, and low self efficacy in the material of Geometry at SMK Negeri 5 Pontianak. The subjects in this research were people, namely students of class XII of SMK Negeri 5 Pontianak who were at high, medium, and low self efficacy. The technique of the data collection is test techniques and direct communication techniques. The data collection tools used are questionnaires, problem questions, and interviews. Obtained from students with high self efficacy can relatively solve problems, can determine plans to solve problems, do calculations well and according to plan, and can re-examine the results obtained and draw conclusions well from the problem proposed; students with medium self efficacy are able to decide questions, determine plans to solve problems, less careful in doing good calculations according to plan, and can re-examine the results obtained and draw conclusions well from the discussion obtained; students with low self efficacy have not been able to solve the problem relatively well, can determine the plan to solve the problem, are not careful in carrying out the calculations and have not been able to draw conclusions well from the problems collected. Keywords: Mathematical Problem Solving Ability, Self Efficacy, Geometry Material.